Efficacy and safety of repetitive transcranial magnetic stimulation for generalised anxiety disorder: A meta-analysis - Cui, Huiru (Gen Psychiatr, 2019)
BACKGROUND: Pharmacological and conventional non-pharmacological treatments are only moderately effective in treating generalised anxiety disorder (GAD). Recently, repetitive transcranial magnetic stimulation (rTMS) has attracted interest because of its potential therapeutic value. AIM: To investigate the efficacy and safety of rTMS treatment for GAD. METHODS: Literature studies published in English or Chinese were screened in 10 electronic databases up to 5 December 2018. The included studies’ bias risk was assessed using Cochrane risk of bias assessment tool. Meta-analysis was performed to compute the standardised mean difference (SMD) and risk ratio (RR) along with its 95% CIs through using RevMan V.5.3. Heterogeneity was inspected by I(2) and the χ(2) test. We performed subgroup analysis and meta-regression to investigate heterogeneity. We used funnel plot to assess publication bias. We used the GRADE approach to assess the whole quality of evidence. RESULTS: Twenty-one studies, with a total sample size of 1481, were analysed. The risk of bias in most studies included is moderate, the majority of which are lacking of blinding methods of treatment allocation. The treatment had beneficial effects in the rTMS group compared with the control group in mean anxiety score (SMD=−0.68; 95% CI −0.89 to −0.46). None of the 21 studies included here reported severe adverse events. As for dropout rates, there are no statistically significant differences between the two groups (RR 1.14, 95% CI 0.72 to 1.82) or adverse events (RR 0.95, 95% CI 0.77 to 1.18). No particular influence on the heterogeneity of any variable was observed. The risk of publication bias was low. According to the GRADE approach, the evidence levels of primary outcome (treatment effects) and secondary outcomes (acceptability and safety) were rated as ‘medium’. CONCLUSION: The use of rTMS combined with medication treatment may have a significant positive anti-anxiety effect on patients with GAD. However, we should interpret the results cautiously due to the relatively high heterogeneity of the meta-analysis. Future high-quality clinical trials are needed to confirm our results.